Upgrade Kernel-2.4.22nptl Menjadi Kernel-2.6.11-6mdk Pada Redhat 9.0 - Noer Wahid; Estiarto Wahyu Sumirat; Dimas Sasongko - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2008)
ABSTRACTHave been known by operating system is organizer all resource found on system and provide a group of service (system calls) to user so that facilitate and protect use and also computer system resource exploiting.In this case one operating system (OS) that is Linux, conception declaration Linux at source open concept. Source Open can be interpreted open code, its intention that is program which have been made can be obtained in the form of its genuinees by its other party apart from the program maker side. Other concept that is General Public License (GPL), Shareware And Freeware. With GPL license this means an software can be joined, to be modified, to be distributed by other party, without there is demarcation from its maker content.Part of Linux operating system consist of kernel, system program and some application program. Kernel represent core from operating system arranging use of memory, input / output, and process usage of file at system file.From result of this new kernel upgrade expected by operating system which have been upgraded by no bug and there no mistake at LILO / grub. Keyword : Kernel, Lilo / grub, Open Source System